The role of modularity in sustainable design: A systematic review. (1st March 2018) - Sonego, Monique; Echeveste, Márcia Elisa Soares; Galvan Debarba, Henrique
Abstract: Modularity is a strategy recognized by the academia and the industry, and modular architecture is argued to play an important role in the development of sustainable products. The objective of this article is to explore the intersection between modularity and sustainable design from the perspective of the product life cycle. To achieve this objective, a systematic review was conducted and a total of 81 articles were selected and distributed in seven different categories of subjects: Life Cycle Assessment, Design for X, Green Modularization, Manufacture, Modularization Reviews, Supply Chain, and Usage. We identified in the literature that: (i) benefits are claimed in every life cycle phase (production, use, and disposal); (ii) academic research is mainly focused in the production phase and in projecting product disposal scenarios, offering a wide variety of methods and methodologies to modularize products with environmental concerns. However, modularity could also present limitations, and the realization of its benefits is partially influenced by user's decisions. Our conclusion points that, in spite of the association of modularity with environmental benefits, a better understanding of the entire life cycle of modular products and their environmental impact is needed to decide whether modularization is a suitable sustainable strategy or not. Highlights: The objective is to overview the relation of modularity with sustainable design. Categories of subjects and benefits through the life cycle were identified. Modularity has limitations and is not always suitable as a sustainable strategy. Few studies approach the environmental performance of modular products in the use. Users have great influence on the environmental benefit achieved through modularity.